2012 7th IEEE International Conference on Nano/Micro Engineered and Molecular Systems (NEMS) 2012
DOI: 10.1109/nems.2012.6196853
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Concern: On the effect of width of metallic armchair graphene nanoribbons in plasmonic waveguide applications

Abstract: Graphene demonstrates superior electronic properties that make it a potential candidate for future electronic systems. Graphene, additionally, support surface plasmon oscillations, which in turn makes graphene at tractive for optoelectronics because of its planar structure and its conductivity properties. When a graphene layer is confined in one dimension, a graphene nanoribbon arises, with proerties differing from the original two dimensional graphene. In this paper we study the main properties of plasmon osc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 86 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…The majority of existing studies [58,68,47,29] are focused on infinitely large graphene sheets. Only recently in [128], the dielectric function of GNRs is utilized to investigate SPP waves in metallic AGNRs. Next, we capture the impact of the finite width of AGNRs and the chemical potential on the SPP waves.…”
Section: Analytical Studymentioning
confidence: 99%
“…The majority of existing studies [58,68,47,29] are focused on infinitely large graphene sheets. Only recently in [128], the dielectric function of GNRs is utilized to investigate SPP waves in metallic AGNRs. Next, we capture the impact of the finite width of AGNRs and the chemical potential on the SPP waves.…”
Section: Analytical Studymentioning
confidence: 99%
“…The nanoscale thickness and planar footprints of metasurfaces enable their fabrication using single-step lithography technologies and allow them to take full advantage of mature semiconductor industries. So far, the research community has demonstrated numerous high-performance metasurfaces exhibiting a chain of functionalities including beam shaping [26], high-resolution imaging [27][28][29], metaabsorbers [30][31][32][33], asymmetric light transmission [34][35][36][37], hologram projection [38][39][40][41][42][43][44], and structured light generation [45][46][47][48][49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%